ABO blood groups, rhesus factor and pemphigus - Valikhani Mahin; Kavand Sima; Toosi Siavash; Kavand Golnaz; Ghiasi Maryam (Wolters Kluwer Medknow Publications, 2007)
Background: Pemphigus is an autoimmune blistering disease of the skin and mucous membranes with significant mortality and morbidity. Genetic factors are known to be involved in pemphigus. Several studies have reproducibly shown significant associations of ABO blood groups with various autoimmune human diseases. Aim: To study the relationship between ABO and Rhesus (D) blood groups and pemphigus in Iranian patients. Materials and Methods: Data on age, sex, ABO and Rhesus blood type and clinicopathological diagnosis of the patients with pemphigus were collected. A total of 573 patients with pemphigus were assessed for their association with ABO or Rhesus (D) blood groups and compared with the normal population in the area. Results: The distribution of ABO and Rhesus blood groups in patients with pemphigus was similar to the normal local population in Iran. No relationship was found between ABO or Rhesus blood groups and the phenotype of pemphigus. Conclusion: It appears that there is no association between ABO or Rhesus (D) blood groups and the frequency of pemphigus variants in comparison with normal population in Iran.